Efekty realizacji działania „Poprawa przetwórstwa i marketingu artykułów rolnych” w przedsiębiorstwach przemysłu mięsnego - Szwech, Agnieszka (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
Sectoral Operational Programme Restructuring and Modernization of the Food Sector and Rural Development (SOP AGRICULTURAL) in 66% co-financed by EU funds and in 34% from the national budget, was one of the tools of agricultural policy in Poland in the first period after accession. As a part of this program 15 measures were implemented. One of these measure was called: “Improving in processing and marketing of agricultural products”, with a budget of 0.5 billion EUR, which made a quarter the entire programme budget. The support for processing under the SOP AGRICULTURAL consisted in the capital expenditures reimbursement to companies for construction or modernization of production facilities and infrastructure for wholesale trade in agricultural products. One of the conditions indispensable to receive support was the economic viability – i.e. the ability of companies to implement the project and to the further continuation of profitable business in the sector. The aim of the article is to present the results of “Improving in processing and marketing of agricultural products” under the SOP of Agriculture in the meat industry sector, by analyzing the financial performance of companies that have benefited from support. The study complies 20 companies from the area of five provinces from Central Poland and North-East of Poland: warmińsko - mazurskie, podlaskie, lubelskie, mazowieckie and łódzkie. Companies were divided into three groups, taking as a criterion for division the value of their assets in the base year of 2004. The study results show that some enterprises, improved financial results in line with the program. These are companies with value of assets ranging from 30 to 90 million zł. The smaller companies (asset value to 30 million zł) observed decline in financial performance. Financial situation of the largest companies (assets in excess of 90 million zł) did not change.